RepRapable Recyclebot: Open source 3-D printable extruder for converting plastic to 3-D printing filament. (October 2018) - Woern, Aubrey L.; McCaslin, Joseph R.; Pringle, Adam M.; Pearce, Joshua M.
Graphical abstract: Abstract: In order to assist researchers explore the full potential of distributed recycling of post-consumer polymer waste, this article describes a recyclebot, which is a waste plastic extruder capable of making commercial quality 3-D printing filament. The device design takes advantage of both the open source hardware methodology and the paradigm developed by the open source self-replicating rapid prototyper (RepRap) 3-D printer community. Specifically, this paper describes the design, fabrication and operation of a RepRapable Recyclebot, which refers to the Recyclebot's ability to provide the filament needed to largely replicate the parts for the Recyclebot on any type of RepRap 3-D printer. The device costs less than $700 in mate rials and can be fabricated in about 24 h. Filament is produced at 0.4 kg/h using 0.24 kWh/kg with a diameter ±4.6%. Thus, filament can be manufactured from commercial pellets for <22% of commercial filament costs. In addition, it can fabricate recycled waste plastic into filament for 2.5 cents/kg, which is <1000X commercial filament costs. The system can fabricate filament from polymers with extrusion temperatures <250 °C and is thus capable of manufacturing custom filament over a wide range of thermopolymers and composites for material science studies of new materials and recyclability studies, as well as research on novel applications of fused filament based 3-D printing.